PELATIHAN KETRAMPILAN BERBICARA BAHASA INGGRIS PADA “GIVING & ASKING DIRECTION” BAGI IBU-IBU PURI BURAN INDAH KARANGANYAR - Widyashanti Kunthara Anindita (Gapenas Publisher, 2021)
English as the language of international communication today is significant to be learned by students and homemakers. Housewives, especially PBI (Puri Buran Indah) Rt.7/Rw.6 mothers also need to be given English lessons. This is so that they can increase confidence when they can practise speaking English if foreigners are confused in finding a tourist location or asking for help with an address. The CLT (Communicative Language Teaching) method emphasizes the interaction between learners and teachers in achieving predetermined learning goals in this direction. The results of this training mothers feel happy because they get knowledge and practice it directly. Although the Javanese accent of mothers is still there when speaking English but it is not a problem. Most importantly, PBI mothers have no problem with what they want to say or speak English in terms of directions